BAR Excavation in Jerusalem Highlights Summer Seminar - Fleming, James (The Biblical archaeology review, 1979)
The following report was prepared by Jim (Yaakov) Fleming, BAR’s Jerusalem correspondent and Director of BAR’s Summer Seminar in Israel.